Sofosbuvir as a drug in recurrent HCV therapy occurring after liver transplantation - Lipa, Katarzyna; Jabłońska, Magdalena Julia; Kaczor, Patryk; Leis, Kamil; Kałużny, Krystian; Gałązka, Przemysław (Journal of Education, Health and Sport, 2018)
Sofosbuvir is a drug, which has been found useful in HCV (Hepatis C Virus) therapy. It replaced the previously used interferon, the applied of which has shown many side effects or lack of response to treatment. The usage of sofosbuvir with ribavirin shortens the time of treatment and minimizes the number of side effects. It is taken as a single dose of 400 mg for 12 or 24 weeks. The only place of activation of this prodrug is hepatocytes, where its active metabolite is formed (GS-461203). It should not be used together with P-glycoprotein inductors that can reduce the efficiency of its action and with amiodarone, because application of both of them together slows down the heart rate. Numerous tests have demonstrated the effectiveness of sofosbuvir in the treatment of patients who have relapsed disease after liver transplantation. A high percentage of sustained virologic response obtained in all phases of clinical trials has proven the efficacy of sofosbuvir in combination with ribavirin or another HCV drug in the therapy of hepatitis C infection.